Cloning and Expression of a Thermostable-α Glucosidase - A. Mohamed, Rauda (2010)
Yeast is considered as a good host for large scale production of enzymes. This is the first report of α-glucosidase obtained from bacterial source to be expressed in yeast.Seven bacterial isolates were successfully obtained from water sample of Telaga Air Hangat, Langkawi. The optimum growth temperature for these bacterial isolates (L2,L3, L4, GBB1, SR 38, SR 40 and SR 96) was at 55oC. Screening using an α-MUG plate overlay method indicated that 4 out of 7 isolates gave positive α-glucosidase activity (L2, L3, L4 and GBB1). The highest activity was 1.47 U/mL at 55°C from sample L3. This isolate was identified using 16S rRNA as a universal primer and from the BLAST result, the isolate showed 99% similarity to Geobacillus stearothermophilus. The gene encoding α-glucosidase was isolated from this identified bacterium using degenerate primers. A complete gene sequence encoding α-glucosidase (~1.7 kb) was obtained by a DNA walking approach. This gene fragment was successfully cloned and expressed into Escherichia coli Top10 cells using pBAD and pTrcHis2@TOPO TA expression vectors. The intracellular α-glucosidase production by recombinant E. coli was increased 3.4-fold and 2-fold in pBAD and pTrcHis2 compared to the wild type isolate, respectively. The restriction enzymes (RE) based primers were designed to clone the gene into a yeast expression vector pPICZαA and to allow transformation into P. pastoris. Transformation was successfully achieved with the α-glucosidase expression level at 3.3 U/mL before optimization. After optimization, the highest activity obtained was ~10 U/mL. This is about 2-fold higher than the expression by E. coli and 6-fold higher than the wild type isolate. P. pastoris expression system was shown to be effective in increasing the expression yield of the heterologous protein